2022
DOI: 10.1038/s41598-022-11091-1
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of hydrogen-rich water intake and hydrogen gas inhalation on gut microbiome and plasma metabolites of rats in health status

Abstract: The potential for preventive and therapeutic applications of H2 have now been confirmed in various disease. However, the effects of H2 on health status have not been fully elucidated. Our previous study reported changes in the body weight and 13 serum biochemical parameters during the six-month hydrogen intervention. To obtain a more comprehensive understanding of the effects of long-term hydrogen consumption, the plasma metabolome and gut microbiota were investigated in this study. Compared with the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Specifically, both MGH and CMG treatments significantly enhanced phenylalanine and tyrosine metabolism, which are known to be closely linked to oxidative stress response ( Ipson et al, 2019 ). Our findings are consistent with a previous study that reported significant alternations in the fecal microbiota of rats following hydrogen gas treatment, leading to increased phenylalanine, tyrosine and tryptophan biosynthesis ( Xie et al, 2022 ). The gut microbiome plays a role in regulating intestinal functions through its metabolites, including hydrogen gas and SCFAs.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, both MGH and CMG treatments significantly enhanced phenylalanine and tyrosine metabolism, which are known to be closely linked to oxidative stress response ( Ipson et al, 2019 ). Our findings are consistent with a previous study that reported significant alternations in the fecal microbiota of rats following hydrogen gas treatment, leading to increased phenylalanine, tyrosine and tryptophan biosynthesis ( Xie et al, 2022 ). The gut microbiome plays a role in regulating intestinal functions through its metabolites, including hydrogen gas and SCFAs.…”
Section: Discussionsupporting
confidence: 93%
“…A wide diversity of gut microbes metabolize H 2 ( 47 ), such that H 2 from C. minuta may boost their growth. Indeed, hydrogen administration to the gut microbiome in drinking water has been shown to alter gut microbial diversity ( 48 , 49 ). Mice receiving hydrogen-water have also been shown to produce greater levels of SCFAs in the cecum ( 50 ), which is consistent with our observations of greater cecal SCFAs in Live-CM treated female mice.…”
Section: Discussionmentioning
confidence: 99%
“…As redox modulation is known to play a crucial role in de novo lipogenesis [ 27 ], the anti-oxidative activity of coral hydrate might be related to the measured decreases in serum triglycerides. Alternatively, changes in the gut microbiome might mediate lipid metabolism [ 28 ] to produce the observed effects, since consumption of hydrogenated water alters gut microbiome and plasma metabolites in rats [ 29 ]. Thus, coral hydrate might not only directly regulate lipid metabolism in the liver, but it may also affect lipid metabolism indirectly through changes in the gut microbiome.…”
Section: Discussionmentioning
confidence: 99%